The Effectiveness of The Ta'lim Program in Strengthening Islamic Religious Education for Students - Adela, Nur; Ritonga, Asnil Aidah (Nazhruna: Jurnal Pendidikan Islam, 2023)
This study aims to test the effectiveness of the ta'lim program in strengthening Islamic religious education using a mixed method, a combination of quantitative and qualitative approaches. The sampling technique used is simple random sampling. The data collection technique used in this study was a questionnaire with a population of 665, taking a sample of 30 students. The questionnaire results explained that 18 questions on variable X were declared valid, and on variable Y, all were declared valid. In the Reliability Test, Cronbach's alpha Reliability Statistics data of 0.817 > 0.6 shows that the variable instrument of the effectiveness of the ta'lim program is reliable. There is a significant linear relationship between the variable efficacy of the ta'lim program (X) and the variable of strengthening Islamic education (Y) obtained from the significance value of deviation from linearity is 0.203, which means greater than 0.05. The results of this study show that variable X (Effectiveness of ta'lim program) affects variable Y (Strengthening Islamic Education) by 12%, and other things outside the variable influence the additional 88%.